Modelling the long term sustainability impacts of coordination policies for urban infrastructure rehabilitation ... - Pericault, Youen; Viklander, Maria; Hedström, Annelie (Zenodo, 2023)
Python code and input data for the research article: "Modelling the long term sustainability impacts of coordination policies for urban infrastructure rehabilitation" published in Water Research journal with DOI: https://doi.org/10.1016/j.watres.2023.119912 File description: murp.py : File to be run to launch the simulation. Murp stands for Multi-Utility Rehabilitation Planner murm.py : File contained the murm function called by the murp script. Murm stands for Multi-Utility Rehabilitation Modeller. Cost.xlsx, Cost_env.xlsx, Header_Length.xlsx, Header_Cohort.xlsx, Header_installation_year.xlsx, Survival_coeff_a.xlsx, Survival_coeff_b.xlsx, Survival_coeff_c.xlsx : input files used in the publication for the case study of Luleå Residential streets. Files starting with "header" contain only the 10 first lines of the input file used in the simulation. ...